Preparation and Characterization of Low-Cost Bio-Sorbent and a Novel Activated Carbon from Agro-Wastes for Efficient Cr(VI) Removal - Erdem, Mehmet; Oner, Ayseguel (Springer Int Publ Ag, 2025)
This study focuses on the preparation and characterization of a novel highly efficient activated carbon (new-AC) and a low-cost adsorbent (BM) from a mixture of agro-based wastes to remove toxic Cr(VI). BM was obtained by mixing wastes subjected to some specific preparation processes in equal proportions, while new-AC was produced by pyrolyzing BM chemically activated with KOH. Various techniques such as elemental analysis, BET-surface area (SBET), pore size and volume measurements, pHpzc, FTIR, Boehm titration, and SEM-EDX analysis were employed for the characterization of adsorbents. The findings revealed that new-AC exhibited a greater SBET, carbon content, and more acidic surface (1413 m2/g, 91.9% C, and pHpzc of 6.8) compared to BM (5.32 m2/g, 51.08% C, and pHpzc of 7.8). Adsorption experiments were performed to evaluate the efficiency of each adsorbent, with results compared against a commercial activated carbon (com-AC) for Cr(VI) removal. The optimal conditions for removing 50 mg-Cr(VI)/L were identified as pH 2, 4 g/L dosage, and 30 min contact time for new-AC; pH 2, 5 g/L dosage, and 90 min for com-AC; and pH 2, 20 g/L dosage, and 60 min for BM. The maximum adsorption capacities observed for BM, new-AC, and com-AC were 6.46, 51.55, and 41.67 mg/g of Cr(VI), respectively. The adsorption behavior for all three adsorbents aligned well with the Langmuir isotherm model, and thermodynamic analysis suggested that the adsorption processes were exothermic, spontaneous, and favorable.
Keywords: Activated carbon; Adsorption; Agro-waste; Bio-sorbent; Hexavalent chromium